Sistem Pendukung Keputusan Pemilihan Kualitas Songkok Berdasarkan Bahan Baku Menggunakan Metode Naïve Bayes - Mochamad Ainun Rozaq; Nur Nafi'iyah; Masruroh Masruroh (LPPM Universitas Mercu Buana Yogyakarta, 2019)
In determining the quality of skullcap with criteria including boss-bored, velvet, inner layers, layers of cloth. And there are several types of quality, namely super, premium, standard and low. The purpose of making a skullcap quality Determination system is to be able to help the production department in the production of skullcaps and marketing. Because if the process of determining the production is done using human labor, it is susceptible to fatigue and doubt because of the limitations of human capability. To reduce the obstacles that occur needed a desktop-based system that can help determine the quality of skull cap. The purpose of this research is to develop a decision support application system to determine the quality of songkok and how to determine the quality of songkok by using the naïve bayes method. The data used in this study were 300 training dataset lines and 54 testing dataset with 74,5% accuracy.